Lamellar Ceramic Semicrystalline‐Polymer Composite Fabricated by Freeze Casting1 . Issue 8 (15th May 2017) - Huang, Jiacheng; Xu, Zhe; Moreno, Salvador; Morsali, Seyedreza; Zhou, Zhong; Daryadel, Soheil; Baniasadi, Mahmoud; Qian, Dong; Minary‐Jolandan, Majid
Abstract : Understanding the role of ductile polymer phase in mechanical behavior of bioinspired hybrid composites is an important step toward development of materials with damage tolerant properties. Herein, the authors report on fabrication and characterization of a bioinspired lamellar composite by incorporation of a semicrystalline polymer into a freeze casted scaffold. The elastic modulus and ductility of the polymer phase can be changed by more than three and 55 times, respectively, in addition to 42 folds decrease in modulus of toughness, by thermal annealing post‐processing, after infiltration into the freeze casted ceramic scaffold. The results show that although polymer phase affects the fracture toughness and flexural behavior of the composite, the drastic changes in mechanical properties of the polymer phase has only marginal effect in the resulted properties of the composite. The authors use in situ SEM experiments and finite element simulation to investigate the deformation mechanism and the effect of the polymer phase on the distribution of stress in the fabricated composites. Abstract : Directional freeze casting and vacuum infiltration is used to fabricate lamellar ceramic‐polymer composites using ceramic micro‐platelets and a semicrystalline polymer. Effect of thermal annealing on the morphology and properties of the polymer phase and its effect on mechanical properties of the fabricated composited is investigated.